2012
DOI: 10.1100/2012/170345
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Project P.A.T.H.S. in the Junior Secondary School Years: Objective Outcome Evaluation Based on Eight Waves of Longitudinal Data

Abstract: To assess the effectiveness of the Tier 1 Program of the Project P.A.T.H.S., a randomized group trial with eight waves of data collected was carried out. At the fifth year of data collection, 19 experimental schools (n = 2, 662 students) and 24 control schools (n = 3, 272 students) participated in the study. Analyses based on individual growth curve modeling showed that participants in the experimental schools displayed better positive youth development than did participants in the control schools in terms of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 33 publications
2
52
0
Order By: Relevance
“…Various evaluative studies involving different stakehold ers have shown that the program is overwhelmingly suc cessful in reducing secondary school students' problem behaviors (e.g., substance abuse, Internet addiction, delinquent behaviors, etc.) and in improving their per formance on a wide range of positive youth develop ment indicators, including prosocial behavior, positive identity, moral competence, and bonding (48)(49)(50)(51). These findings provide sound evidence for the effectiveness of positive youth development approach in addressing youth issues and promoting holistic development in young people.…”
Section: Character Strengthsmentioning
confidence: 61%
“…Various evaluative studies involving different stakehold ers have shown that the program is overwhelmingly suc cessful in reducing secondary school students' problem behaviors (e.g., substance abuse, Internet addiction, delinquent behaviors, etc.) and in improving their per formance on a wide range of positive youth develop ment indicators, including prosocial behavior, positive identity, moral competence, and bonding (48)(49)(50)(51). These findings provide sound evidence for the effectiveness of positive youth development approach in addressing youth issues and promoting holistic development in young people.…”
Section: Character Strengthsmentioning
confidence: 61%
“…A step-by-step approach was adopted by using LISREL. Research indicates the importance of family functioning and positive youth development in influencing adolescent developmental outcomes [9][10][11][12][13][14][15]. Built on the literature, this article attempts to demonstrate the longitudinal relationships among family functioning, positive youth development qualities, and consumption of pornography over time.…”
Section: Introductionmentioning
confidence: 96%
“…Clearly, our study sheds light on the understanding of employing this advanced statistical technique in longitudinal research. Further applications of IGC using SPSS can be seen in other papers generated from this study [37,38]. The statistical technique plays an important role in the evaluation of positive youth development programs [39].…”
Section: Discussionmentioning
confidence: 98%